Molecular Docking of Gallic Acid and Its Derivatives as the Potential nNOS Inhibitors - Sulistyaning Budi; Annisa Fitri Nurlaila; Icaq Dwi Prasetyo; Indah Nur Rahmadhani; Javier Sebastian; Iqmal Tahir (Jurnal Kimia Sains dan Aplikasi, 2022)
The global prevalence of anxiety and depression rates have increased by 25% due to the impact of the COVID-19 pandemic. Depression can occur due to an increase in NO produced by the nNOS enzyme. Gallic acid and its derivatives can be obtained from nature and have various biological activities. This study aimed to determine the potential of gallic acid and its derivatives as nNOS inhibitors using the molecular docking method with parameters of binding energy values, RMSD values, and specific binding to amino acid residues. The results showed that gallic acid, 4-O-methyl gallic acid, and epigallocatechin gallate had bond energies of −1.87; −2.36; and −0.12 kcal/mol, respectively. Compared to the standard ligand, which had binding energy of −2.84 kcal/mol, gallic acid 4-O-(6-galloyl glucoside) had binding energy of −4.12 kcal/mol. Based on these results, gallic acid 4-O-(6-galloyl glucoside) can potentially inhibit nNOS.